\left\{ \begin{array} { c } { 2 x + 5 y - z = 1 } \\ { - x + y + 5 z = - 13 } \\ { x + y - z = 3 } \end{array} \right.
Solve for x, y, z
x=2
y=-1
z=-2
Share
Copied to clipboard
z=2x+5y-1
Solve 2x+5y-z=1 for z.
-x+y+5\left(2x+5y-1\right)=-13 x+y-\left(2x+5y-1\right)=3
Substitute 2x+5y-1 for z in the second and third equation.
y=-\frac{9}{26}x-\frac{4}{13} x=-4y-2
Solve these equations for y and x respectively.
x=-4\left(-\frac{9}{26}x-\frac{4}{13}\right)-2
Substitute -\frac{9}{26}x-\frac{4}{13} for y in the equation x=-4y-2.
x=2
Solve x=-4\left(-\frac{9}{26}x-\frac{4}{13}\right)-2 for x.
y=-\frac{9}{26}\times 2-\frac{4}{13}
Substitute 2 for x in the equation y=-\frac{9}{26}x-\frac{4}{13}.
y=-1
Calculate y from y=-\frac{9}{26}\times 2-\frac{4}{13}.
z=2\times 2+5\left(-1\right)-1
Substitute -1 for y and 2 for x in the equation z=2x+5y-1.
z=-2
Calculate z from z=2\times 2+5\left(-1\right)-1.
x=2 y=-1 z=-2
The system is now solved.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}